Biomimetics: teaching the tools of the trade - Kristina Wanieck; Daniel Ritzinger; Cordt Zollfrank; Shoshanah Jacobs (FEBS Open Bio, 2020)
Biomimetics is a known innovation paradigm of the twenty‐first century with significant impact on science, society, economy, and challenges of sustainability. As such, it can be understood as a mindset for creative thinking and as a methodology or technique for effective knowledge transfer between disciplines, mainly biology and technology. As biomimetics is relevant to practitioners in various fields of application, understanding the teaching and training of biomimetics for different audiences is important. With this article, we aim to give a holistic view of teaching and training practices and opportunities. First, we offer a set of learning objectives based on an analysis of various courses worldwide and we give recommendations for the design of future curricula. Second, based on an audience analysis and interviews, we developed a set of personas of the users of biomimetics, and as such, we offer a deeper understanding of their needs for the design of the process, including tools and methods.